Economic integration among the members of the League of Arab States: an empirical evidence - Mohd Amin, Ruzita; Hamid, Zarinah; Md Saad, Norma (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2005)
This article investigates the extent of economic integration among five members of the League of Arab States , namely Egypt, Jordan, Saudi Arabia, Sudan and Syria, by empirically testing the nature of intra-trade activities in the grouping. Five of their major trading partners are included in the study, i.e., France, Germany, Italy, the UK and the US. The gravity model is used in the scaled and unscaled forms. Both pooled and yearly estimations for the period 1991 to 2002 are performed. The results indicate that the LAS economic grouping has not been effective in trade creation, indicating failure of integration measures undertaken. The article recommends tariff reductions and the provision of better infrastructure to increase intra-trade activities among LAS members.